URBAN REHABILITATION OF THE CITY CENTER OF ORAN (ALGERIA): A RECONCILIATION WITH THE COLONIAL HERITAGE? - Fatima Zohra Bekri; Brahim Nouiabat; Sid-Ahmed Souiah (International Journal of Innovative Technologies in Social Science, 2024)
This research paper delves into the emerging interest in heritage preservation concerning the rehabilitation of buildings inherited from the colonial era in the city center of Oran. It addresses several key aspects: an examination of the urban history of Oran and the development of its city center, tracing the architectural and urban planning movements that have influenced it. Particularly, it explores the reappropriation of spaces following Algeria’s independence in 1962, marked by the significant exodus of the European population and the subsequent implementation of a rental system managed by a public entity, the Office of Promotion and Real Estate Management. A postcolonial retrospective allows for an analysis of the degradation resulting from this management approach and the subsequent deterioration of buildings since the full transfer of ownership of these "State Assets" in 1981. The initial diagnosis, conducted in 2008, emphasizes the urgency for public intervention and justifies the subsequent rehabilitation efforts.